Psychometric Properties of the General Self-efficacy Scale in Indonesian Senior High School Students: Invariance Across Gender - Amalia Rizki Pautina; Mungin Eddy Wibowo; Heru Mugiarso; Awalya; Arif Sahin (Bisma The Journal of Counseling, 2025)
The measurement instruments assessing self-efficacy among Indonesian high school students have yet to establish cultural relevance and measurement equivalence across gender groups, raising the potential for biased gender comparisons. Without strong psychometric evidence, the interpretation of research findings and the design of educational interventions remain limited. This study aimed to adapt and comprehensively evaluate the psychometric properties of the Indonesian version of the General Self-Efficacy Scale (GSES) and to examine its measurement invariance across gender. Using a cross-sectional survey design, data were collected from 635 students and analyzed through Confirmatory Factor Analysis (CFA) and multigroup procedures to assess configural, metric, scalar, and strict invariance. The results supported a three-factor, ten-item solution, with satisfactory model fit indices (CFI = 0.943; RMSEA = 0.066; SRMR = 0.043) and high internal consistency (Cronbach’s α = 0.85). Measurement invariance testing confirmed gender equivalence across all levels. In conclusion, the adapted Indonesian version of the GSES demonstrated strong validity and reliability for assessing self-efficacy among high school students. The findings suggest that this instrument is suitable for use in research, educational assessment, and the development of interventions and policies aimed at enhancing students’ motivation, resilience, and academic outcomes.